2016
DOI: 10.1080/07481187.2016.1155675
|View full text |Cite
|
Sign up to set email alerts
|

Suicidality among immigrants: Application of the interpersonal-psychological theory

Abstract: Immigrants constitute a significant percentage of the total population living in the United States; however, there is a paucity of research unique to suicidality among immigrants. The present article examines the applicability of the three variables of the interpersonal-psychological theory of suicidal behavior-acquired capability for suicide, sense of thwarted belongingness, and perceived burdensomeness-to conceptualize, assess, and treat suicidality among immigrants. Risk and protective factors and mechanism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 62 publications
0
28
0
Order By: Relevance
“…Country of birth appears to play a role in the risk for suicide ideation and suicide attempting. In a multi-country study, 27 out of 56 immigrant groups in Europe had significantly higher suicide attempt rate than the host populations in the respective countries [39]. Another study found that there was no significant difference in suicide attempting between Western European immigrants and locals [40].…”
Section: Area Of Residencymentioning
confidence: 99%
“…Country of birth appears to play a role in the risk for suicide ideation and suicide attempting. In a multi-country study, 27 out of 56 immigrant groups in Europe had significantly higher suicide attempt rate than the host populations in the respective countries [39]. Another study found that there was no significant difference in suicide attempting between Western European immigrants and locals [40].…”
Section: Area Of Residencymentioning
confidence: 99%
“…One of the most influential theories related to suicide is Thomas Joiner's interpersonal-psychological theory of suicidal behavior (IPT) (Kene et al, 2016). Joiner's IPT of suicidal behavior has been widely used in behavioral research with various populations (Kene et al, 2016). The framework posits that the following three states of mind are necessary for suicide to occur in a person: acquired capability of suicide, perceived burdensomeness, and a sense of thwarted belongingness (Joiner, 2005;Kene et al, 2016).…”
Section: Attitudes Toward Suicide: Theoretical Perspectivesmentioning
confidence: 99%
“…Joiner's IPT of suicidal behavior has been widely used in behavioral research with various populations (Kene et al, 2016). The framework posits that the following three states of mind are necessary for suicide to occur in a person: acquired capability of suicide, perceived burdensomeness, and a sense of thwarted belongingness (Joiner, 2005;Kene et al, 2016). Acquired capability involves a fearless person with increased pain tolerance through repeated exposure to painful and provocative events, such as suicide attempts; violence, substance use, or prostitution; a history of physical or sexual abuse; and a history of mental illness (Kene et al, 2016).…”
Section: Attitudes Toward Suicide: Theoretical Perspectivesmentioning
confidence: 99%
“…Trauma in the migratory process itself may provide the habituation to pain and acquired suicide capacity. 12 The process of problematic acculturation in young migrants may lead to perceptions of thwarted belongingness from valued social groups such as neighbours and community, which in turn predisposes them to negative emotions towards the self and passive suicidal ideation.…”
mentioning
confidence: 99%
“…It also increases the probability of elevated anxiety, depression and numerous other psychiatric symptoms into young adulthood, predisposing migrants to suicidal ideation. 12,1518 Thus, most adolescent migrants and their families are beset with the stress of acclimation and acculturalisation within a frequently hostile environment, while their dreams of a better life are attacked from all quarters, including from within the family. 19…”
mentioning
confidence: 99%